2000
DOI: 10.1021/es991422f
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Reduction of 2,4,6-Trinitrotoluene and Related Nitroarenes: Kinetics Linked to One-Electron Redox Potentials

Abstract: At military bases and munitions factories, 2,4,6-trinitrotoluene (TNT) is a common soil and groundwater contaminant. Although the reduction of nitro groups in TNT and related nitroarenes has been extensively investigated, few researchers have studied the link between reduction rates and the electrochemical properties of these compounds. In this work, the standard one-electron redox potentials at pH 7 (E 1 °‘) for six important nitroarenes have been measured by pulse radiolysis. The internally consistent values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…Similar values were obtained by a pulse radiolysis study (-0.397 V) (Riefler and Smets 2000) and LFER employing H 2 S as the reductant (-0.360 V) (Dunnivant and Schwarzenbach 1992), affording average of -0.38 ± 0.02 V for four independent approaches.…”
Section: One-electron Reduction Potential Of 24-dntsupporting
confidence: 80%
“…Similar values were obtained by a pulse radiolysis study (-0.397 V) (Riefler and Smets 2000) and LFER employing H 2 S as the reductant (-0.360 V) (Dunnivant and Schwarzenbach 1992), affording average of -0.38 ± 0.02 V for four independent approaches.…”
Section: One-electron Reduction Potential Of 24-dntsupporting
confidence: 80%
“…From the change in NADH and nitroarene concentrations, the stoichiometry of reactant consumption was determined while the NADH consumption profile was translated into a nitroarene consumption profile. Details of this method have been reported previously (48). NAD ؉ inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have reported the accumulation of hydroxylamino compounds (15,33,46,48), and hydroxylamino and nitroso intermediates may abiotically condense to azoxy dimers that persist (24,27,28,40). TNT is also susceptible to aerobic hydrogenation of the aromatic ring.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several prokaryotic FMN-dependent enzymes have received recent attention because they reductively eliminate nitrite from xenobiotic explosive compounds, which can serve as a sole source of nitrogen (Spain, 1995;Binks et al, 1996;Blehert et al, 1997Blehert et al, , 1999French et al, 1998;Nivinskas et al, 2000;Riefler & Smets, 2000;Williams & Bruce, 2000;Barna et al, 2001;Ebert et al, 2001;Meah et al, 2001;Haynes et al, 2002;Johnson et al, 2002;Khan et al, 2002;Koder et al, 2002;Williams & Bruce, 2002;Orville, Manning, Blehert, Studts et al, 2004). Thus, it appears that the reductive enzymes enable some microorganisms to exploit nitrochemicals introduced into the environment by recent human activities.…”
Section: Introductionmentioning
confidence: 99%